FACTORS INCREASING DIVORCE RATES DURING THE COVID-19 PANDEMIC IN LAMPUNG PROVINCE - Yulia Hesti; Nuraini Hasanah Sudrajat (Law Faculty of Universitas Bandar Lampung, 2021)
The increasing number of divorce rates that occur is of particular concern, especially the government and during this COVID-19 pandemic, the divorce rate in Lampung Province has increased very significantly. In the course of marriage, there will definitely be problems faced by husband and wife where problems that cannot be resolved will inevitably lead to a divorce. Divorce is usually marked by several factors. The factors causing the increase in divorce rates during the COVID-19 pandemic in Lampung Province were disputes and also quarrels caused by several things, namely Financial Problems, Child Absence, Infidelity, Communication and Differences. It is hoped that husband or wife will understand each other better and understand the conditions that occur, especially if it is associated with the ongoing covid-19 pandemic.